1996
DOI: 10.1021/ja954015m
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Activation Energy for Luminescence Decay:  Specific Solvation Effects on the Emission Properties of Bis(2,2‘-bipyridine)(3,5-dicarboxy-2,2‘-bipyridine)ruthenium(II) Chloride

Abstract: A new mixed-ligand polypyridylruthenium(II) complex, [Ru(bpy) 2 L]Cl 2 , has been prepared where bpy ) 2,2′-bipyridine and L ) 3,5-dicarboxy-2,2′-bipyridine. The ligand L is a non-symmetrically-substituted 2,2′-bipyridine having two hydrophilic carboxylate groups located at the 3-and 5-positions of only one of its two pyridyl rings. In acetonitrile, the photophysical properties of the metal complex include a long-lived excited state (λ em ) 637 nm, τ) 846 ( 11 ns, φ ) 0.046 at 295 K) whose decay involves an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…916 All of these methods, however, suffer from one or more important limitations, including lack of air-stability of the 2-pyridyl building blocks, 10,1216 use of toxic metals, 9 inability to isolate the building blocks in chemically pure form, 11 and/or inefficient couplings with more challenging halide coupling partners such as deactivated aryl chlorides. 11,12,13b17 Overcoming all of these limitations, we herein report the first general solution for the 2-pyridyl problem.…”
mentioning
confidence: 99%
“…916 All of these methods, however, suffer from one or more important limitations, including lack of air-stability of the 2-pyridyl building blocks, 10,1216 use of toxic metals, 9 inability to isolate the building blocks in chemically pure form, 11 and/or inefficient couplings with more challenging halide coupling partners such as deactivated aryl chlorides. 11,12,13b17 Overcoming all of these limitations, we herein report the first general solution for the 2-pyridyl problem.…”
mentioning
confidence: 99%
“…12a In preliminary studies, however, we were only able to achieve a low yield of 1a from 3 . 3e For example, the dropwise addition of a freshly prepared THF solution of 3 to a stirred suspension of MIDA in DMSO at 55 °C over 1 hour (Fig.…”
mentioning
confidence: 87%
“…10 Many different types of surrogates for 2-heterocyclic boronic acids have been developed, including trifluoroborate salts, 11 trialkoxy or trihydroxyborate salts, 12 diethanolamine adducts, 13 sterically bulky boronic esters, 14 and boroxines. 15 Important advances with 2-heterocyclic silanolates have also recently been reported.…”
mentioning
confidence: 99%
“…126 Interestingly, the synthesis of the sensitive dimethyl 2-pyridylboronate 77 was not described in detail until five years later, followed by the application in a cross-coupling reaction with 78 giving the disubstituted 2,2 0 -bipyridine 79 (Scheme 21). 127 Until the turn of the millennium only few investigations into the synthesis of 2-pyridylboron compounds have been reported. Terashima et al reported synthetic investigations on dialkylpyridylboranes, including the diethyl(2-pyridyl)borane (80).…”
Section: General Considerationsmentioning
confidence: 99%